2000
DOI: 10.1099/00221287-146-10-2555
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of DNA–protein intermediates during activation of the Pu promoter of the TOL plasmid of Pseudomonas putida

Abstract: The ATP-dependent multimerization process undergone by the σ 54 -dependent activator XylR of the TOL plasmid pWW0 of Pseudomonas putida when bound to the upstream activating sequences (UAS) of the cognate Pu promoter was examined by transmission electron microscopy (TEM). To this end, supercoiled DNA templates were combined with increasing concentrations of the constitutive XylR variant XylR∆A, with or without ATP or its non-hydrolysable analogue ATPγS, and the resulting complexes were visualized by TEM. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…NtrC subunits inside this complex may have increased ATPase activity, and the complex itself will interact with the 54 RNA polymerase-promoter complex, resulting in transcriptional initiation. For XylR, it has been proposed that in the presence of ATP, the protein-DNA structures seem to constantly assemble and disassemble between octamers and two dimer pairs (7). This scenario could explain why no higher-order structures of activated HbpR and the UAS C-1 and C-2 fragments were visible in GMSAs, as the equilibrium was mostly on the side of the dimer pair interaction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…NtrC subunits inside this complex may have increased ATPase activity, and the complex itself will interact with the 54 RNA polymerase-promoter complex, resulting in transcriptional initiation. For XylR, it has been proposed that in the presence of ATP, the protein-DNA structures seem to constantly assemble and disassemble between octamers and two dimer pairs (7). This scenario could explain why no higher-order structures of activated HbpR and the UAS C-1 and C-2 fragments were visible in GMSAs, as the equilibrium was mostly on the side of the dimer pair interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Upon activation of the regulatory protein, the differences in the binding affinities for each of the UASs increase strongly (25,31). In the current activation model, it is assumed that there is continuous cycling among the inactive dimer in solution, the inactive two-dimer pair on the UAS DNA, and the octameric (active) complex (7). XylR itself is supposed to follow more or less the same model as NtrC, except that activation of the protein takes place through effector binding and not through phosphorylation.…”
mentioning
confidence: 99%
“…Although a number of bacterial transcription factors have been shown to form oligomers (31)(32)(33)(34)(35), there are only limited examples from eukaryotes. As mentioned, proteins that contain a POZ domain, such as GAGA, have been implicated in oligomer formation (29,36).…”
Section: Figmentioning
confidence: 99%
“…The levels of XylR⌬A in P. putida MAD2 remained relatively constant (variation is below ϳ1.5 times) in stationary phase regardless of 3-MBA addition, and no extra bands were detected. Taken together, these experiments revealed that even during exponential growth phase, when produced from single gene copies per chromosome of P. putida, the number of available XylR or XylR⌬A monomers per cell (ϳ28 Ϯ 5 for XylR and 90 Ϯ 9 for XylR⌬A) exceeds by at least 1 order of magnitude the number of DNA targets (upstream activating sequences [UAS]) (12) in the cell. The intracellular XylR and XylR⌬A levels further increase by fivefold in the stationary phase of growth, coinciding with the activity of the Pu promoter.…”
Section: Vol 183 2001mentioning
confidence: 99%